2015
DOI: 10.1177/0340035215580278
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, perception and attitude of Nigerian students to plagiarism

Abstract: This study investigated the knowledge, perception and attitude of Nigerian students to plagiarism. The instrument for data collection was a structured questionnaire which was self administered by the researchers to the respondents. The respondents were 282 first year students in the Faculty of Business Administration, University of Nigeria, Enugu Campus. The collected data was analyzed with frequency counts and percentage. The major findings show that the knowledge of plagiarism among the students prior to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 14 publications
2
30
0
3
Order By: Relevance
“…If the students had high knowledge about plagiarism, it can be made them avoiding plagiarism. This study showed that most students came into the university with average skills in research and writing, and it still possible that students can commit plagiarism intentionally or unintentionally (Onuoha & Ikonne, 2013;Ibegbulam, I. J., & Eze, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the students had high knowledge about plagiarism, it can be made them avoiding plagiarism. This study showed that most students came into the university with average skills in research and writing, and it still possible that students can commit plagiarism intentionally or unintentionally (Onuoha & Ikonne, 2013;Ibegbulam, I. J., & Eze, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…They were also asked to write down their own opinion if they thought their reason was not on the list. Both of the questionnaires were adapted from (Ibegbulam & Eze, 2015) and (Lei & Hu, 2015) for knowledge of plagiarism. While for questionnaire for the reason why graduate students committing plagiarism, the statements were adapted from Razera (2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the students had high knowledge about plagiarism, it can be made them avoiding plagiarism. This study showed that most students came into the university with average skills in research and writing, and it still possible that students can commit plagiarism intentionally or unintentionally (Onuoha & Ikonne, 2013;Ibegbulam & Eze, 2015).…”
Section: Rodhiyamentioning
confidence: 99%
“…Findings from studies carried out by several researchers (Agu et al, 2009;Orim, 2011;Orim, 2014;Ibegbulam & Eze, 2015;Olutola, 2016) in Nigerian Higher Institutions of learning suggest that there are occurrences of student plagiarism. As reviewed in several other sources earlier, this finding is not peculiar to the Nigerian Higher Institutions of Learning.…”
Section: ) Promoting Academic Integritymentioning
confidence: 99%